(untitled) (The Agriculturists, 2012)
A field experiment was conducted at the Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh during winter season, 2007 - 2008 to determine the effects of N and B on the yield and hollow stem disorder of broccoli. Four levels of N as 0, 60, 120, 180 kg ha-1 and four levels of B as 0, 0.5, 1.0 and 1.5 kg ha-1 constituting sixteen treatments were applied in a split plot design with three replications. Applied N and B had significant impact on the yield and hollow stem disorder of broccoli. The highest curd yield of 15.14 t ha-1 was obtained by 180 kg N ha-1. The incidence of hollow stem disorder was increased by increasing rate of N application and the highest value of hollow stem index of 1.38 was found with 180 kg N ha-1. The curd yield of broccoli was significantly increased with boron application up to 1.0 kg ha-1. This rate thus showed a remarkable impact on reduction of hollow stem disorder. A moderately high amount of B application (1.0 kg ha-1) led to minimum incidence of hollow stem disorder, attaining considerably lowest value of hollow stem index of 1.0 as against the maximum value of 1.16 under no application of B. The interaction effect of N and B on yield and quality of broccoli was significant and the highest yield (16.68 t ha-1) was recorded under 180 kg N and 1.0 kg B ha-1, which might be recommended for farmers practice in the Shallow-Red-Brown Terrace Soil of Madhupur Tract. DOI: http://dx.doi.org/10.3329/agric.v10i2.13140 The Agriculturists 2012; 10(2) 36-45